Collaborative development of reusable educational resources for software engineering and information systems core subjects. (21st February 2011) - Orta, Elena; Ruiz, Mercedes; Hurtado, Nuria; Garcia, Ma. Teresa; , Jose Luis Isla
In the context of the European Higher Education Area adaptation process, a group of teachers of the Computer Science degree of the University of Cadiz have developed an initiative for the collaborative creation of a set of educational resources that are used or supplemented in diverse courses of software engineering and information systems core subjects. This initiative has been implemented as the proposal of a project, which has been accepted in the context of a call for higher education innovation projects for teachers and researchers and is developed along the academic year 2008/2009.